Analysis and Tunable Models for Phosphor-Converted White Light-Emitting Diode Based on Spectral Compensation - Xuehua Shen; Huanting Chen; Wenjie Zhang; Xiaoxi Ji; Yan Yi (IEEE Photonics Journal)
The correlated color temperature (CCT) and color rendering index (CRI) are two significant indicators related to the color appearance and visual effects of illumination. This paper concentrates on dynamic dimming for phosphor-converted (PC) white LEDs to achieve tunable CCT and adequate CRI, via compensation of red/green spectra. The LED systems described have a simple configuration consisting of a PC white LED, a monochrome green LED and a monochrome red LED, which can be individually driven. Compared to individual PC white LEDs, both the spectral continuity and uniformity of the mixed white light are enhanced. The tunable dimming models are proposed by combination of spectral colorimetry and photo-electro-thermal (PET) theory, thus multi-physics effects are involved. From the modeling process and results, the nonlinear characteristics are observed. Experimental verifications present good agreement existing between calculations and measurements, both in terms of values and variation trends. These proposed models could be effective tools to figure out photometric characteristics and visual perception of illumination. On the other hand, they could provide schemes of reference to improve the illumination environment adapting to various special occasions and personal preferences.